2017
DOI: 10.1108/cg-06-2016-0129
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between corporate governance mechanisms and IFRS 7 compliance: evidence from an emerging market

Abstract: Purpose This paper aims to investigate compliance with risk disclosure requirements under International Financial Reporting Standard (IFRS 7) by firms listed on the Ghana Stock Exchange (GSE) over a three-year period. Specifically, the paper examines the extent, quality and determinants of risk disclosure compliance with IFRS 7. Design/methodology/approach The study uses 90 firm-year observations for the period 2011-2013 for firms listed on the GSE. Each annual report was individually examined and coded to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 61 publications
8
41
1
1
Order By: Relevance
“…Risk reporting literature has not been conclusive on the relationship between RRD and independent non-executive directors. Some studies have found a positive association (Abraham and Cox, 2007;Ntim et al, 2013;Agyei-Mensah, 2017), but others did not find any significant association (Elzahar and Hussainey, 2012;Buckby et al, 2015;Elshandidy and Neri, 2015;Allini et al, 2016;Singh, 2017). In the Portuguese context, Oliveira et al 2011found a positive association.…”
Section: Board Independencementioning
confidence: 99%
See 4 more Smart Citations
“…Risk reporting literature has not been conclusive on the relationship between RRD and independent non-executive directors. Some studies have found a positive association (Abraham and Cox, 2007;Ntim et al, 2013;Agyei-Mensah, 2017), but others did not find any significant association (Elzahar and Hussainey, 2012;Buckby et al, 2015;Elshandidy and Neri, 2015;Allini et al, 2016;Singh, 2017). In the Portuguese context, Oliveira et al 2011found a positive association.…”
Section: Board Independencementioning
confidence: 99%
“…Prior literature on the influence of corporate governance mechanisms and RRD are focused on Anglo-Saxon countries (Taylor et al, 2010;Abraham and Cox, 2007;Elzahar and Hussainey, 2012;Ntim et al, 2013), developing Islamic/African countries (Mokhatar and Mellet, 2013;Agyei-Mensah, 2017), India (Singh, 2017) and European Latin countries (Oliveira et al, 2011;Elshandidy and Neri, 2015;Allini et al, 2016;Madrigal et al, 2015;Carmona et al, 2016), using different explanatory variables to assess different aspects of the same constructs (such as board composition, ownership structure, and audit committee). (Oliveira et al, 2011), Italy (Elshandidy and Neri, 2015;Allini et al, 2016) and Spain (Madrigal et al, 2015;Carmona et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations